„ANSWER TO KEMPNER” BY KARL SCHMITT AS A HISTORICAL LESSON OF PHILOSOPHICAL, LEGAL AND POLITICAL COMPETENCE OF „THE LAST GREAT CLASSIC” - Шумський, Л.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Commentary of fragments of little-known to domestic researchers of Karl Schmitt work „The Answer to Kempner" (the chief prosecutor deputy at Nuremberg judgment) is a way to show scientific-theoretical validity of cogitative strategy of „the last great classic" in an initial context on understanding of the philosophical and legal importance of institutes of a state system in the spirit of the times, and also to characterize political and didactic aspects in the intellectual heritage of this scientist, which are actual for specifics of Ukrainian discourse space.